ANALISIS STRATEGI GURU DALAM MENGELOLA PERILAKU TANTRUM PADA ANAK USIA DINI DI TK KRISTEN “BAIK” PAPUA - Ludia Napan; Varia Virdania Virdaus (Universitas Narotama, 2026)
This study aims to describe the forms of tantrums that occur in early childhood and analyze teacher strategies in managing tantrum behavior in the